DAMPAK WORK OVERLOAD TERHADAP STRES KERJA DAN TURNOVER INTENTION DENGAN LEADERSHIP SUPPORT SEBAGAI VARIABEL MODERASI - Ezzah Nahrisah; Ani Murwani Muhar; Zuwina Miraza; Feri Ramadani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This Research is based on the high operational costs incurred by the company in carrying out business activities so that PT. Pacific Medan Industri need to make efficiency. This directly puts pressure on employees. Excessive workloads and poor communication between leaders and employees cause work stress which results in the desire of employees to leave the company. The purpose of this study was to determine the effect of workoverload on work stress and turnover intention through leadership support as a moderating variable at PT. Pacific Medan Industri.This research was conducted using a quantitative approach with regression methods, single test and MRA (Moderated Regression Analysis). The data used are primary data obtained through questionnaires to 105 respondents. Based on the test result, it was found that work overload had no significant effect on work stress, work overload had a significant positive effect on turnover in intention, work stress mediated work overload on turnover intention and leadersip support doesn’t moderated work stress on turnover intention